From Policy to the Periphery: A Look at India’s National Rural Health Mission - Dhillon, Sheiry (The Meducator, 2012)
Sheiry is a third year student in the Global Health Specialization of the Bachelor of Health Sciences (Honours) Program. She spent this past summer in Northern India’s Himalayan region completing a research project for Jagori Grameen, a local non-governmental organization. The central focus of her research was to understand the various rural health standards set by the Indian government and to examine whether primary health centers in the district of Kangra, Himachal Pradesh, are meeting these standards